2020
DOI: 10.1007/s11682-020-00319-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring decline in white matter integrity after systemic treatment for breast cancer: omitting skeletonization enhances sensitivity

Abstract: Chemotherapy for non-central nervous system cancers is associated with abnormalities in brain structure and function. Diffusion tensor imaging (DTI) allows for studying in vivo microstructural changes in brain white matter. Tract-based spatial statistics (TBSS) is a widely used processing pipeline in which DTI data are typically normalized to a generic DTI template and then 'skeletonized' to compensate for misregistration effects. However, this approach greatly reduces the overall white matter volume that is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Previously, it was assumed that adjuvant chemotherapy exerts a direct toxic effect on oligodendrocytes and CNS progenitor cells that cause brain damage, and therefore the term “Chemical Brain” or “Chemobrain” was created [ 19 ]. However, later changes in the integrity of the white matter were also found after other treatment regimens including radiotherapy, chemotherapy and, therefore, the term was changed to “cancer-related cognitive impairment” [ 20 , 21 ]. Several theories exist to try to explain the mechanisms of the treatment-related brain damage, but the etiology of the CNS damages is most likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was assumed that adjuvant chemotherapy exerts a direct toxic effect on oligodendrocytes and CNS progenitor cells that cause brain damage, and therefore the term “Chemical Brain” or “Chemobrain” was created [ 19 ]. However, later changes in the integrity of the white matter were also found after other treatment regimens including radiotherapy, chemotherapy and, therefore, the term was changed to “cancer-related cognitive impairment” [ 20 , 21 ]. Several theories exist to try to explain the mechanisms of the treatment-related brain damage, but the etiology of the CNS damages is most likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have explored the biological mechanism of the cognitive effects of chemotherapy drugs in small animals ( 9 , 10 ). Neuroimaging plays an important role in neuropathology mechanistic research ( 11 , 12 ), and with the development of magnetic resonance imaging (MRI) techniques, the detection of related morphological changes has become more convenient and contributed to understand some of chemotherapy-related cognitive impairment (CRCI) ( 13 15 ). An increasing number of neuroimaging studies have shown that the pathological cognitive symptoms of patients are particularly related to the altered structure of gray matter (GM) and abnormal brain volume, although the relationship between brain aging in patients with CRCI and biomarkers of neuroimaging is still only the tip of the iceberg ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described neurotoxicity associated with chemotherapy agents. Neuroimaging studies have characterized diffuse structural changes in the brain following chemotherapy, such as significant white matter integrity changes and widespread abnormalities in gray matter volume [11][12][13][14][15][16]. Task-based functional MRI (fMRI) has demonstrated functional abnormalities in brain areas associated with cognitive function [17,18].…”
Section: Introductionmentioning
confidence: 99%